1975
DOI: 10.1073/pnas.72.2.474
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration that monocytes rather than lymphocytes are the insulin-binding cells in preparations of humah peripheral blood mononuclear leukocytes: implications for studies of insulin-resistant states in man.

Abstract: Insulin receptors have been demonstrated on mononuclear leukocytes prepared by centrifugation of buffy coats from normal blood donors on Ficoll-Hypaque gradients. The cell type that specifically binds insulin in this mixture of lymphocytes and monocytes has never been clearly identified, although it was assumed to be the lymphocyte since this cell constitutes about 80%/c of the population. In the present studies, insulin-binding assays were performed on the mononuclear leukocyte preparation before and 'after s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
56
0
1

Year Published

1978
1978
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(61 citation statements)
references
References 27 publications
4
56
0
1
Order By: Relevance
“…However, we do not detect differences in 125Tg B cell responses when either hormonally active or inactive insulin is used (not shown). In addition, previous studies have shown that mAb125 does not recognize InsR-bound insulin (52) and that resting T and B cells do not express InsR (53). However, both BCR and InsR traffic in clathrin vesicles; thus, it remains possible that some interactions in the endosomal pathway generate signals during intracellular processing.…”
Section: Discussionmentioning
confidence: 99%
“…However, we do not detect differences in 125Tg B cell responses when either hormonally active or inactive insulin is used (not shown). In addition, previous studies have shown that mAb125 does not recognize InsR-bound insulin (52) and that resting T and B cells do not express InsR (53). However, both BCR and InsR traffic in clathrin vesicles; thus, it remains possible that some interactions in the endosomal pathway generate signals during intracellular processing.…”
Section: Discussionmentioning
confidence: 99%
“…Insulin receptors have been demonstrated on alloimmune T cells [23] and circulating monocytes [24]. In addition, evidence has been presented that insulin can augment lymphocyte-mediated cytotoxicity [25] and modulate Fc-mediated phagocytosis by monocytes [26] and macrophages [27].…”
Section: Discussionmentioning
confidence: 99%
“…They were then suspended in 100 mmol/ 1 Hepes buffer containing i g/100 ml bovine serum albumin (BSA) (pH 7.8). The mononuclear cell preparation contained 85% lymphocytes and 15% monocytes [18]; since it has been demonstrated that insulin binding depends primarily upon monocytes [21,22] 0012-186X/80/0019/0118/$01.00 Relationship between percent labelled insulin combined to antibody and subsequent binding of labelled insulin (0.2 ng/ml) to placenta membranes (150 ~xg/ml). Maximal receptor binding (i. e. 100%) was evaluated using labelled insulin pre-incubated for 48 h at 4 ~ in sodium phosphate buffer and was 31.2% of total radioactivity.…”
Section: Preparation Of Insulin-free Serummentioning
confidence: 99%